Protein kinases - Woodgett, James Robert (Oxford ; New York : IRL Press at Oxford University Press, 1994)
Frontiers in Molecular Biology is a series of books designed to report on rapidly evolving, key areas of molecular biology research. Individual chapters are written by leading researchers who are specialists in their fields. Each book is carefully organized to provide an integrated analysis of current progress in the area covered.
Protein kinases share a unique catalytic function and are involved in virtually all regulated processes, from ion transport and metabolic pathways to DNA replication and differentiation. They act as powerful transducers of information, amplifying weak signals or integrating complex messages. Above all, they are the primary mechanism for acute coordination of the myriad of processes that continuously flux during the life cycle of the cell.
The daunting progress made in the last decade in this area has been encapsulated in this book, written by established experts in the field. Protein Kinases presents detailed, up-to-date discussions of structural, functional, and genetic aspects of protein phosphorylation research. It is essential reading for all those interested in signal transduction and the control of cellular processes by protein phosphorylation.
Includes bibliographical references and index.
Keywords: Protein kinases; Protein Kinases